Confini di-versi Frontiere, orizzonti e prospettive della poesia italofona contemporanea - Pisanelli, Flaviano (Moderna/Comparata, 2019)
This book is dedicated to the poetics in the Italian language that have spread around Italy over the last thirty years, also as a consequence of the migratory waves from the South-East to the North-West of the world. After years of research, the authors have selected a sample of twelve poets, who for different reasons have adopted Italian as the language of their literary expression. These authors come from the Balkans (Bosnia and Herzegovina, Albania), from Eastern Europe (Romania, Poland), from central-northern Europe (Austria, Germany), but also from Latin American countries (Brazil, Argentina , Chile), the Middle East (Iran and Iraq), and the Africa (Senegal). This volume features a long critical introduction and an updated bibliography, and studies the issue of migration from a cultural, literary and linguistic perspective, further investigating the work of individual poets in relation to their culture of origin and their use of the language (or languages), touching current and complex notions and issues such as otherness, interculturality, evolution of identity, migration and relationship between the multicultural and multilingual writing and the contemporary Italian poetic tradition and its canon. The unpublished interviews concluding the volume were made at the authors' places of residence and reconstruct their biographical and artistic path and their idea of language, translation, literature, home country and nationality.